Rede de interações aves-plantas arbóreas em fragmentos de floresta ripária na região noroeste do Paraná. - Castro, Sáuria Lúcia Rocha de (2011)
Seed dispersal mediated by animals is an essential process to the life cycle of plants. In natural communities, species and their interactions are arranged in non-random networks with complex, repeated and distinct patterns. This study was conducted in three fragments of riparian forest in the northwest of Paraná State in order to describe the interaction network between frugivorous birds and tree plant species. Sampling occurred monthly from January 2009 to March 2010, except in June and July. Interactions involved 18 plant species and 43 bird species, totaling 420 observation hours. The interaction network was constructed based on 338 feeding events. There was a large number of specialist species simultaneously promoting a low connectance and modular and nested patterns in the network. Eight modules were identified and Cecropia pachystachya was the only module hub. The nested pattern indicates that specialist plants are dispersed by generalist birds, while specialist and generalist birds disperse generalist plants. It was found that phylogenetically close birds do not necessarily interact with the same plants. Turdus leucomelas was the most generalist bird, interacting with six plant species, while Cecropia pachystachya had the highest number of interactions (35). In this study, there was predominance of non-forest bird species interacting strongly with pioneer plant species. This reflects the conservation state of the fragments, which present vegetation in early successional stage.